2020
DOI: 10.4103/sajc.sajc_111_19
|View full text |Cite
|
Sign up to set email alerts
|

The real-world experience with nivolumab in previously treated patients with advanced non-small cell lung cancer from a cancer center in India

Abstract: Background: PDL-1 inhibitors have emerged as the new standard of care for second line treatment of NSCLC. Methods: Eligible patients included, histologically proven NSCLC, ECOG (Eastern Cooperative Oncology Group) performance status of 0, 1 or 2, age 18 years and above, availability of pre-treatment tumor specimen, adequate end organ function, at least one prior platinum-based therapy. Patients who received a minimum of 6 doses of nivolumab were eligible. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 74%
See 1 more Smart Citation
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 74%
“…Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23]. There were no particular differences between real world experiences from Asian or non-Asian countries.…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 74%
“… 21 Nevertheless, three additional real-world studies of nivolumab were excluded from this review due to the sample size restriction. 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced NSCLC has a very poor outcome, with a mean expected survival of about 7 months [25]. Immune checkpoint inhibitor (ICI) therapy for NSCLC seems to increase the patients' survival to a range between 8 and 15 months [26][27][28]. Nonetheless, the increase in the immune response induced by ICIs can cause secondary effects related to an unbalanced homeostasis of the systemic immune system [29].…”
Section: Introductionmentioning
confidence: 99%